2016
DOI: 10.1590/abd1806-4841.20164632
|View full text |Cite
|
Sign up to set email alerts
|

Trichosporon isolation from human ungueal infections: is there a pathogenic role?

Abstract: BACKGROUNDAlthough dermatophytes are considered the major cause of onychomycosis, many reports have incriminated non-dermatophyte moulds and yeasts in the disease’s etiology. Successive Trichosporon isolation from onychomycosis has led to the genus being suspected as a nail primary pathogen.OBJECTIVETo determine the prevalence of Trichosporon isolation in onychomycosis patients who attended a mycology diagnostic service in Rio de Janeiro, Brazil, between January 2003 and December 2006. The study also includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Trichosporon species have rarely been implicated as causative agents of onychomycosis. 14,15 We detected a 1.7% frequency for Trichosporon isolation from onychomycosis, mainly Trichsporon species isolates (75%); other authors have reported frequencies varying from 0.54% to 8% for Trichosporon in different countries. 15,16 Although T asahii is implicated as a systemic disease-associated pathogen, we were able to isolate Trichosporon species at a noticeable frequency, as a single microorganism, from onychomycosis in patients living in Turkey.…”
Section: Discussionmentioning
confidence: 54%
“…Trichosporon species have rarely been implicated as causative agents of onychomycosis. 14,15 We detected a 1.7% frequency for Trichosporon isolation from onychomycosis, mainly Trichsporon species isolates (75%); other authors have reported frequencies varying from 0.54% to 8% for Trichosporon in different countries. 15,16 Although T asahii is implicated as a systemic disease-associated pathogen, we were able to isolate Trichosporon species at a noticeable frequency, as a single microorganism, from onychomycosis in patients living in Turkey.…”
Section: Discussionmentioning
confidence: 54%
“…[84][85][86] Yeast-like fungi, such as Kodamaea ohmeri (Previously Pichia ohmeri or Yamadazyma ohmeri) Trichosporon and Rhodotorula, have been reported to be common causal agents of onychomycosis. [87][88][89][90] Other yeast-like fungi, such as Geotrichum and Cryptococcus, have also been known to cause cutaneous infections. [91][92][93][94] Dimorphic fungi (existing either as mycelium when present in the environment or as yeast or spherules at host body temperature) usually cause endemic mycoses, such as blastomycosis (Blastomyces dermatitidis and Blastomyces gilchristii), coccidioidomycosis (Coccidioides immitis and Coccidioides posadasii), paracoccidioidomycosis (Paracoccidioides brasiliensis and Paracoccidioides lutzii), sporotrichosis (Sporothrix schenckii) and histoplasmosis (Histoplasma capsulatum).…”
Section: Ae Ti Olog I C Al Ag Ents For Superfi Cial Mycos E Smentioning
confidence: 99%
“…These include factors, like, moisture, temperature, the composition of sebum, perspiration, age, specific skin chemistry, heavy exposure or contact with infected body parts and genetic predisposition. 90,221,222 It has been reported that the patients living in rural areas show more frequency (57%) than those from urban areas (43%). 36,58,150,223,224 It may be attributed to more awareness among the urban people along with greater accessibility to medical care.…”
Section: Cultur Al and Environmental Fac Tor S Re S P On S Ib Le For Superfi Cial M Ycos E Smentioning
confidence: 99%
See 1 more Smart Citation
“…After that, some mycologists recovered other species of Trichosporon also as common agents of onychomycosis from different parts of the world and their frequency ranged from 0.87% to 8.0% . Among the various Trichosporon species, T. cutaneum was recovered as nail pathogen from Nigeria, Denmark and Leipzig/Alemanha, whereas T. mucoides , T. capitatum, T. inkin , T. ovoides and T. dohaense were recovered as etiological agents of onychomycosis from different parts of the globe by Mugge et al, Souza et al, Taj‐ Aldeen et al, Sageerabanoo et al, Ortega‐Sprigall et al, Capoor et al, de Magalhaes et al and Rizzitelli et al …”
Section: Discussionmentioning
confidence: 99%